2017
DOI: 10.1080/15321819.2017.1351372
|View full text |Cite
|
Sign up to set email alerts
|

cag Pathogenicity island-dependent upregulation of matrix metalloproteinase-7 in infected patients with Helicobacter pylori

Abstract: Helicobacter pylori (H. pylori) infection has been involved in the pathogenesis of most important gastroduodenal diseases. Matrix metalloproteinases (MMPs) are a large family of zincendopeptidases which play important roles in degradation of extracellular matrix (ECM) and various inflammatory diseases. Therefore, we examined MMP-7 mRNA levels in the gastric mucosa of patients with H. pylori infection and evaluated the effects of virulence factors, such as vacA (vacuolating cytotoxin A) and cagA (cytotoxin-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…An increase of MMP-7 levels in gastric biopsy specimens from patients infected with H. pylori has been demonstrated by several studies [43][44][45][46]. In contrast to MMP-9, MMP-7 localizes preferentially on the surface of epithelial cells and deep in the gastric gland, where chief cells are distributed [43].…”
Section: Mmp Levels and Localizationmentioning
confidence: 92%
See 1 more Smart Citation
“…An increase of MMP-7 levels in gastric biopsy specimens from patients infected with H. pylori has been demonstrated by several studies [43][44][45][46]. In contrast to MMP-9, MMP-7 localizes preferentially on the surface of epithelial cells and deep in the gastric gland, where chief cells are distributed [43].…”
Section: Mmp Levels and Localizationmentioning
confidence: 92%
“…Among bacterial factors responsible for MMPs synthesis and secretion in inflamed gastric mucosa, cagPAI but not VacA has been described in in vivo investigations [46]. In particular, Wu et al [55] have demonstrated that MMP-1 mRNA was overexpressed in samples from gastritis patients infected with cagPAI-and OipA-positive H. pylori.…”
Section: Bacterial Factors and Host Pathways Pivotal For Mmp Activationmentioning
confidence: 99%
“…One hundred and twenty-two specimens were collected from patients with dyspepsia referred to endoscopy center of Shahrekord Hajar Hospital, Iran, from June 2013 to March 2014. All patients were given consent about the procedure before their inclusion, in accordance with the Helsinki Declaration (8). Exclusion criteria were: age lowers than 18-year-old or more than 70, pregnancy, diabetes type-1, systemic infection, use of drugs effective against H. pylori in 1 month ago, alcohol abuse and chronic corticosteroid or nonsteroidal antiinflammatory drug use.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction kit (BioFlux, Japan) was used For Genomic DNA extraction from all samples. The PCR protocol for CagA, OipA gene evaluation was done according to the previous study (8,12,13). To measure IL-32 mRNA expression, real-time PCR was performed, the designed primers and probes were shown in table 2.…”
Section: Histological Examinationmentioning
confidence: 99%
See 1 more Smart Citation